IT- integrated design collaboration engagement model in support of Malaysian building design professionals - Delavari, Naeimeh (2011)
Design collaboration is an activity that requires the participation of various individuals to accomplish an agreed design task or goal. Globalization is what has changed the character of this field, integrating geographically dispersed participants through the Internet or an intranet server. Professional design team members can now communicate via collaborative tools and utilize technologies beyond physical boundaries and time. However, many design team members fail to utilize these technological developments. This predicament is exacerbated by various issues, such as the misunderstanding that tends to occur when professionals switch from face-toface to technological communication and limited professional education programs on the subject. The purpose of this research was to find a way to engage Malaysian professional architects in IT-integrated collaborations and to improve their interaction with computing systems using the concept of Human Computer Interaction (HCI). It intended to understand how human factors (physical, cognitive, intrinsically or extrinsically motivated) can be used to facilitate and improve the interaction in professional building design and collaborative technologies to achieve a sustainable IT-integrated design collaboration process. This study used Grounded Theory research methodology to develop an ITengagement model to increase architects’ motivation to collaborate using collaborative technologies. Firstly, this study identified current collaborative technologies and how design team members use them. They include Virtual Prototyping (VP) for producing realistic graphical simulations, collaborative Computer-Aided Design (CAD) and Computer Supported Collaborative Work (CSCW) tools such as video conferencing, and shared document management which facilitates the flow of data. In addition, using the existing parameters of engagement from theories of technology adoption and studies of IT-integrated design collaboration, this study determined feedback, control and functionality as the criteria for developing a model of engagement for design team members using ITsupported technology. At the conclusion of this study, feedback was defined as the knowledge that is allocated to the appropriate design team members and the knowledge that is retrieved from other design team members for improving purpose. Meanwhile, control was defined as the control effect of behaviour on a user. Similarly, functionality was defined as the degree of user performance with the computing system and the degree of technological flexibility afforded to the user. Finally, the study identified that in Malaysian building projects, collaborations tend to occur in face-to-face meetings, where Architecture-Engineering-Construction (AEC) design team members communicate by exchanging paper documents, technical drawings and so on. This highlighted a working-culture deficiency with regards to IT-supported technologies in the design collaboration process. Thus, this study contributes towards the development of an IT-integrated design collaboration (IT-DC) engagement model for Malaysian building design collaborations. It is expected to improve the acceptance of IT-integrated design project collaborations, increase the degree of engagement in collaborative team work projects and support future research to mitigate knowledge losses in complex project lifecycles. This in turn will encourage and facilitate more participation from Malaysian building stakeholders in global projects, thus fulfilling the country’s desire to increase exports in the services industry.